Measuring the Impact of Targeted Food Assistance on HIV/AIDS-Related Beneficiary Groups: Monitoring and Evaluation Indicators - Egge, Kari; Strasser, Susan (International Food Policy Research Institute, 2006)
In October 2005, the Consortium for the Southern Africa Food Security Emergency (C-SAFE) transitioned to its final year of a regional “developmental relief ” program. Yet, members continued to collaborate on this specific learning activity given their common objectives of improving monitoring and evaluation (M&E) for HIV/AIDS-related beneficiary groups. C-SAFE’s strategic objectives included (1) improving and maintaining nutritional status, (2) protecting productive assets, and (3) improving community resilience to food security shocks.